Characterization of T Antigens, Including Middle T and Alternative T, Expressed by the Human Polyomavirus Associated with Trichodysplasia Spinulosa - van der Meijden, Els; Kazem, Siamaque; Dargel, Christina A.; van Vuren, Nick; Hensbergen, Paul J.; Feltkamp, Mariet C. W. (Journal of virology, 2015)
The polyomavirus tumor (T) antigens play crucial roles in viral replication, transcription, and cellular transformation. They are encoded by partially overlapping open reading frames (ORFs) located in the early region through alternative mRNA splicing. The T expression pattern of the trichodysplasia spinulosa-associated polyomavirus (TSPyV) has not been established yet, hampering further study of its pathogenic mechanisms and taxonomic relationship. Here, we characterized TSPyV T antigen expression in human cell lines transfected with the TSPyV early region. Sequencing of T antigen-encoded reverse transcription-PCR (RT-PCR) products revealed three splice donor and acceptor sites creating six mRNA splice products that potentially encode the antigens small T (ST), middle T (MT), large T (LT), tiny T, 21kT, and alternative T (ALTO). Except for 21kT, these splice products were also detected in skin of TSPyV-infected patients. At least three splice products were confirmed by Northern blotting, likely encoding LT, MT, ST, 21kT, and ALTO. Protein expression was demonstrated for LT, ALTO, and possibly MT, with LT detected in the nucleus and ALTO in the cytoplasm of transfected cells. Splice site and start codon mutations indicated that ALTO is encoded by the same splice product that encodes LT and uses internal start codons for initiation. The genuineness of ALTO was indicated by the identification of acetylated N-terminal ALTO peptides by mass spectrometry. Summarizing, TSPyV exhibits an expression pattern characterized by both MT and ALTO expression, combining features of rodent and human polyomaviruses. This unique expression pattern provides important leads for further study of polyomavirus-related disease and for an understanding of polyomavirus evolution. IMPORTANCE The human trichodysplasia spinulosa-associated polyomavirus (TSPyV) is distinguished among polyomaviruses for combining productive infection with cell-transforming properties. In the research presented here, we further substantiate this unique position by indicating expression of both middle T antigen (MT) and alternative T antigen (ALTO) in TSPyV. So far, none of the human polyomaviruses was shown to express MT, which is considered the most important viral oncoprotein of rodent polyomaviruses. Coexpression of ALTO and MT, which involves a conserved, recently recognized overlapping ORF subject to positive selection, has not been observed before for any polyomavirus. As a result of our findings, this study provides valuable new insights into polyomavirus T gene use and expression. Obviously, these insights will be instrumental in further study and gaining an understanding of TSPyV pathogenicity. More importantly, however, they provide important leads with regard to the interrelationship, functionality, and evolution of polyomaviruses as a whole, indicating that TSPyV is a suitable model virus to study these entities further.